(untitled) (Research, Society and Development, 2022)
To quantify amines in ingredients and in different types of feed and to verify spermine inclusion influence in polyamine levels at storage of experimental diets of broiler, ingredients to formulate diets and commercial starting and growth feeds and were purchased. Spermidine, spermine, putrescine, cadaverine, agmatine, tyramine and histamine were detected by ion pair high performance liquid chromatography in ingredients, commercial diets, control and 0.06 and 012% spermine included formulations. Bioactive amines levels were analysed weekly to initial and growth diets, respectively until 21st and 49th days of storage at 26 ± 3°C and 72% relative humidity. All amines were detected in commercial feed. Spermidine and spermine predominate in soybean, wheat and corn, and tyramine in meat and bone meal. To initial diets averages of cadaverine reduced significantly in day 21, except for 0.06% spermine inclusion; agmatine decreased (p<0.05) in times, except for 0.12% spermine inclusion; spermidine were smaller (p<0.05) at 14 and 21 days and increased significantly with the level of inclusion. In growth diets cadaverine oscillated (p<0.05) between 0.35 at 28 days in control and 1.15 mg.100g-1 in 0.06% spermine inclusion at 49 days. Agmatine were 0.36 to 0.91 mg.100g-1 in control; spermidine vary significantly at 7 days in control and in 0.12% spermine inclusion at 28 days; spermine vary from 1.33 at 42 days to control to 72.55 mg.100g-1 at 7 days in 0.12% spermine inclusion. Polyamine levels were low in ingredients, commercial feed and initial and growth experimental formulations even when stored for 21 or 49 days.